Correspondence Between L.N. Tolstoy and A.I. Herzen: Additions to the Scientific Commentary - Evgenija M. Geronimus (Studia Litterarum)
The article examines in detail the correspondence between L.N. Tolstoy and A.I. Herzen by analysis of all publications, in which this correspondence appeared, clarification of the errors that were made when commenting on the letters, and search for a new interpretation of some places of Tolstoy’s and Herzen’s epistolary heritage. The author of the article finds the true name of the French revolutionary chemist Tessier du Motay, who was a close friend of Herzen and was with him in London during Tolstoy’s stay there. The article offers several options for reading the final phrase of Tolstoy’s last letter addressed to a London emigrant, and provides a number of arguments refuting the previous reading. The author of the article proves that the correspondence between Tolstoy and Herzen to this day has a number of “difficult” places, commenting on which can give new information not only about their personal and literary relationships, but also about the realities of that time, the circle of communication between the two thinkers and the historical and social context in which the correspondents were immersed.